2012
DOI: 10.1089/scd.2012.0048
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Colony-Stimulating Factor Stimulation of Bone Marrow Mesenchymal Stromal Cells Promotes CD34+ Cell Migration Via a Matrix Metalloproteinase-2-Dependent Mechanism

Abstract: Human hematopoietic stem/progenitor cells (HSPCs) can be mobilized into the circulation using granulocytecolony stimulating factor (G-CSF), for graft collection in view of hematopoietic transplantation. This process has been related to bone marrow (BM) release of serine proteases and of the matrix metalloproteinase-9 (MMP-9). Yet, the role of these mediators in HSC egress from their niches remains questionable, because they are produced by nonstromal cells (mainly neutrophils and monocytes/macrophages) that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…G-CSFR-positive cells represented 59% of the human pulp stem cells (Murakami M, Horibe H, Iohara K et al, manuscript in preparation). Thus, G-CSF, which stimulates migration of bone marrow mesenchymal stem cells, is based on their expression of G-CSFR [5] and may be a potential alternative to SDF-1 for pulp regeneration. Transplantation of stem cells derived from other tissues, bone marrow stromal cells, neuronal stem cells, and amniotic fluid stem cells, with G-CSF into the spinal cord injury results in a better functional and morphological recovery with augmentation of nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…G-CSFR-positive cells represented 59% of the human pulp stem cells (Murakami M, Horibe H, Iohara K et al, manuscript in preparation). Thus, G-CSF, which stimulates migration of bone marrow mesenchymal stem cells, is based on their expression of G-CSFR [5] and may be a potential alternative to SDF-1 for pulp regeneration. Transplantation of stem cells derived from other tissues, bone marrow stromal cells, neuronal stem cells, and amniotic fluid stem cells, with G-CSF into the spinal cord injury results in a better functional and morphological recovery with augmentation of nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there were no significant differences in those in vitro effects between bFGF and G‐CSF. Enhanced migration of mesenchymal stem cells (MSCs) mediated by bFGF (Langer et al , ) or G‐CSF (Iohara et al , , ; Yu et al , ; Ponte et al , ; Murakami et al , ) has already been demonstrated separately in distinct cell types. The high stimulatory effect on proliferation and differentiation of MSCs into endothelial cells has been elucidated in bFGF‐supplemented medium (Wu et al , ; Wang et al , ) and in G‐CSF‐supplemented medium.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the application of G-CSF, the BM progresses to a highly proteolytic microenvironment that is characterized by MMP-2, MMP-9, MMP-14 (MT1-MMP), cathepsin G, neutrophil elastase, and Cterminal processing cathepsin K and carboxypeptidase M [35,39]. In this situation, CXCL12 may be produced as an important proteolytic CXCL12 variant for stem cell mobilization, which has been suggested to switch receptor specificity to CXCR3 [40,41].…”
Section: Discussionmentioning
confidence: 99%